PHET Interactive Simulation Media Improves Students' Understanding of Mathematical Concepts in Integer Material - Indah Rizky Dwiyanti; Nurafni (MIMBAR PGSD Undiksha, 2023)
Mathematics is a basic science important for humans, but in reality, many students prefer to avoid it because they think mathematics is difficult, abstract, and boring. It can happen because of the ineffectiveness of the learning media educators use, so students need help understanding the concept of mathematical materials. This research was conducted to know how PHET Interactive Simulation media affects students' understanding of mathematical concepts in integer material. This research belongs to the type of experimental research, with the research population being all fourth-grade students. Sampling in the study was carried out using a saturated sampling technique, with a total sample of 67 students consisting of two classes, namely the control and experimental classes. Data collection in the study was carried out using the test method, with the research instrument being a test of understanding mathematical concepts. The data obtained in the study were then analyzed by analyzing the normality test, homogeneity test, and hypothesis testing. This study's results indicate the effect of using PHET Interactive Simulation media on students' understanding of mathematical concepts. It was concluded that there was an effect of using PHET Interactive Simulation media on students' ability to understand mathematical concepts.